Grow with the Flow: When Morphogenesis Meets Microfluidics. Issue 17 (14th February 2019) - Samal, Pinak; van Blitterswijk, Clemens; Truckenmüller, Roman; Giselbrecht, Stefan
Abstract: Developmental biology has advanced the understanding of the intricate and dynamic processes involved in the formation of an organism from a single cell. However, many gaps remain in the knowledge of embryonic development, especially regarding tissue morphogenesis. A possible approach to mimic such phenomena uses pluripotent stem cells in in vitro morphogenetic models. Herein, these systems are summarized with emphasis on the ability to better manipulate and control cellular interfaces with either liquid or solid materials using microengineered tools, which is critical for attaining deeper insights into pattern formation and stem cell differentiation during organogenesis. The role of conventional and customized cell‐culture systems in supporting important advances in the field of morphogenesis is discussed, and the fascinating role that material sciences and microengineering currently play and are expected to play in the future is highlighted. In conclusion, it is proffered that continued microfluidics innovations when applied to morphogenesis promise to provide important insights to advance many multidisciplinary fields, including regenerative medicine. Abstract : How microfluidics can help improve in vitro morphogenetic models is highlighted. These models are an attractive alternative to in vivo embryonic studies, which lack accessibility and are fraught with ethical issues. The current state‐of‐the‐art of the recently developed in vitro morphogenetic models is summarized and the current and future roles that microfluidic systems play in these advancements are discussed.